Researching North Korean Historiography with Digital Humanities Methodologies. - Intae RYU; Jong-wook HONG (Korea Journal)
The purpose of this article is to attempt to combine North Korean humanities research with digital humanities methods, using the North Korean Humanities Data Archive (NKHDA) project as an example, and to report on a newly constructed semantic data processing model. Although NKHDA targeted the entire scope of North Korean humanities, it mainly focused on the field of historiography, which has a relatively large accumulation of scholarly information. This article focuses on North Korean historiography to discuss the following three points. Firstly, the theoretical and technical background of the NKHDA is summarized. Secondly, the trial-and-error process of constructing NKHDA is described. Thirdly, the process of creating a new model of semantic data processing by combining wiki documentation and triple data/visualization is described. A new model was made possible by embedding triple data lists and network graphs into wiki pages and developing a data entry tool for triple data generation. Also described is the NKHDA's use as an educational platform for the digital humanities.